PP.40.18: PREVALENCE OF RESTLESS LEGS SYNDROME IN PATIENTS WITH RESISTANT HYPERTENSION. (June 2015) - Bruno, R.H.; Pengo, M.F.; Di Coscio, E.; Carnicelli, L.; Maestri, M.; Faraguna, U.; Di Galante, M.; Ratneswaran, C.; Leschziner, G.D.; Rossi, G.P.; Cargiolli, M.; Ghiadoni, L.; et al.
Abstract : Objective: Though obstructive sleep apnea syndrome (OSAS) is common in patients with resistant hypertension (RH), the prevalence of other sleep disorders, such as restless legs syndrome (RLS) is unknown. We aimend at investigating the prevalence of OSAS and RLS in a cohort of patients with RH recruited in two centres. Figure. No caption available. Design and method: By using the ESC/ESH definition we consecutively recruited 63 patients with RH (age 63 ± 12 years, BMI 32 ± 6 kg/mq, 24% women, 31% patients with previous CV events, 31% diabetic), undergoing a polisomnographic study. RLS rating scale, Epworth Sleepiness Scale (ESS), past medical history and office BP were obtained. Sleep stages were scored according to 2007 AASM modified criteria. Results: Moderate-severe OSAS (AHI>15/h) was diagnosed in 34 RH patients (54%), RLS in 26 (41%): 13 patients presented both conditions. Only 16 patients (25%) had neither OSAS nor RLS. Periodic limb movements (PLM Index>15/h) were present in 31% of the studied population. OSAS+RLS- and OSAS+RLS+ patients were older than OSAS-RLS- and OSAS-RLS+. None among OSAS-RLS- had diabetes. OSAS+RLS- patients had a reduced total sleep time, sleep and REM latency and sleep efficiency in comparison to OSAS-RLS-. Conversely, slow wave sleep was reduced only in OSAS+RLS+. PLM index was increased in OSAS-RLS+ [18 (0–36)] but not in OSAS+RLS+ [2 (0–25), p < 0.05]. Conclusions: OSAS and RLS are common in RH patients, often co-occurring. BMI or daily sleepiness are not useful to identify RH patients with sleep disorders, suggesting that all RH patients should undergo polisomnography. Diabetes seems to be a feature of RH patients with sleep disorders. When coexisting with OSAS, RLS is not associated with PLM, suggesting a different pathophysiology. However, the presence of OSAS together with RLS is associated with shorter slow wave sleep, a phenomenon that can possibly lead to severe cardiovascular and cognitive complications in this subgroup.